A STUDY ON TRAINING IN CHEMICAL DISASTER MANAGEMENT FOR GOVERNMENT EMPLOYEES IN INDIA - Zine, Ganesh Shankar; Sharma, Bhawna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Chemical disasters pose significant risks to public health, safety, and the environment. Effective disaster management is crucial in mitigating these risks, particularly in a rapidly industrializing country like India. This study aims to explore the effectiveness of training programs in chemical disaster management provided to government employees in India. By examining the current training practices, challenges, and outcomes, this research seeks to provide insights into the preparedness of government employees in handling chemical disasters and to offer recommendations for improving training methodologies. The study also conducted a sample survey on 100 candidates working in various government disaster agencies in Maharashtra region and Mumbai city.